Does androgen deprivation impact associations between cognition and strength, fitness and function in community-dwelling men with prostate cancer? A cross-sectional study. Issue 12 (30th December 2021) - Mundell, Niamh L; Owen, Patrick J; Dalla Via, Jack; Macpherson, Helen; Daly, Robin M; Fraser, Steve F
Abstract : Objectives: We investigated whether there were differences in associations between cognition with muscle strength, fitness and function in men with prostate cancer (PCa) treated with, and without androgen deprivation therapy (ADT) and non-PCa controls. A secondary aim was to compare differences in the prevalence of cognitive impairment. Design: This cross-sectional study compared 70 ADT-treated men with PCa aged 50–85 years to non-ADT-treated men (n=52) and non-PCa controls (n=70). Setting: University clinical exercise laboratory. Interventions: Nil. Primary and secondary outcome measures: Standardised assessments were conducted for cognition (learning, memory, attention, processing speed and executive function), muscle strength (grip strength and leg press), fitness (400 m walk), gait speed (4 m walk) and dual-tasking mobility (timed-up-and-go with a cognitive task). Results: ADT-treated men showed stronger associations between fitness and executive function and task switching relative to controls (both: p≤0.03). For both PCa groups (independent of ADT use), poorer dual-task mobility was more strongly associated with decreased psychomotor attention (both: p≤0.027) and global cognitive function (both: p≤0.031) compared with non-PCa controls. The overall prevalence of cognitive impairment was low (4%–13%) and did not differ between the groups. Conclusions: The presence of PCa, with or without ADT treatment, did not increase the risk of cognitive impairment relative to non-PCa controls, yet did alter the associations between physical fitness and some measures of functional performance with certain cognitive domains. This highlights the importance of men with PCa maintaining fitness and functional capacity to optimise cognitive health. Trial registration number: This study was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12614000317695).